Psychological-pedagogical features of adaptation of today’s first-graders to studying (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the analysis of the problem ofadaptation of today’s first-graders to study at school. The article gives apsychological description of adaptation of first-graders to study, the specifics ofadaptation of first-graders to study under conditions of the program "On theWings of Success". The results of the experimental study of the features of thestudy of the emotional value relation of first-graders to classmates, schools, andeducational activities in the class as indicators of their adaptation to study havebeen illustrated in the article. The results of the comparative analysis of thediagnostics results of the emotional experience of social contacts by thefirst-graders trained under the program "On the wings of success" and underconditions of traditional education have been presented.
Keywords: Adaptation, adaptation of first-graders to study, structural components of adaptation, emotional attitude towards school, educational program